The Contribution of Self-Efficacy by Performing the Skill a Front Handspring on the Mat Floor Movement of Gymnastics for Students - Zaid Sami Yasir; Osma Abdel Moneim Jawad; Yassin Alowan Ismail (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study aimed to identify the level of self-efficacy and the numerical values of the results of the performance of the front hands jump skill on the ground movement rug in the gymnasium of the students, and to identify the percentage of the self-efficacy contribution to the performance of the front hands jump skill on the ground movement rug in the homemaking of the students, the researchers adopted the descriptive approach in the method of relational relations on a sample of (82) students deliberately chosen (89.13%) from their community represented by the third stage students in the Department of Physical Education and Sports Sciences at the College of Basic Education / Al-Mustansiriyah University who are continuing the official working hours for the academic year (2020/2021), the self-efficacy scale, which is specially prepared for students of colleges and departments of physical education and sports sciences, and videography to test the students ’performance of the front hand jump skill on the ground movement rug in the gymnastics was adopted, and the researchers applied these two tools on the sample and processed its results with the (SPSS) system to make the conclusions and applications that the third stage students need In the Department of Physical Education and Sports Sciences in the College of Basic Education to improve the level of selfefficacy and improve their level of performance skill a front handspring on the mat floor movement of gymnastics for students, Self-efficacy is positively related, contributes and affects the improvement of their performance level for this skill, and it is necessary to intensify efforts between teachers of gymnastics and specialists in sports psychology and their cooperation to support raising the level of self-efficacy according to scientific principles that are not improvised because of its important role in improving the performance of the skill a front handspring on the mat floor movement of gymnastics for students.